A comprehensive study for the airborne gamma-rays spectrometry results of Gabal El-Hassnawia, Central Eastern Desert, Egypt - NIGM, Ahmed A.; GHEITH, Baher M.; SHAHEEN, Mohamed A. (Contributions to Geophysics and Geodesy, 2022)
The present study utilizes the airborne gamma-ray spectrometric data of Gabal El-Hassnawia and its vicinity in an attempt to refine the surface geological mapping and recognize the radioelements occurrences. The statistically analysed surface lineaments derived from the Landsat image proved that they are oriented to the NW, NNW, N–S, and ENE trends. Qualitatively, the highest radiometric levels are related to the younger granites, the intermediate levels are observed over the Hammamat sediments and the acidic metavolcanics while the low levels are coinciding with the metasediments, ultramafites and basic to intermediate metavolcanics. The composite images show a good close correlation with the geologically mapped rock units. The factor analysis proved that the radiometric variables uranium (eU), potassium (K) and thorium (eTh) as well as total count (TC) are highly correlated positively with each other. Three principal factors F1, F2 and F3 are extracted from the data and their scores were used in differentiating the rock types according to their radiometric levels; consequently, nine interpreted litho-radiometric units were identified. Three types of younger granites and two types of Hammamat sediments could be distinguished among the nine units. These units are subjected to statistical treatment with the goal of identifying the uranium occurrences that exceeds X + 2S and X + 3S as targets of exploration. Accordingly, it is found that the uranium province zones are related to the three types of granite (G1, G2 and G3), the second type of Hammamat sediment (H2) and more or less the acidic metavolcanics. The uranium migration indicated that the second type of Hammamat sediment (H-2) is the only unit that the uranium is migrated in whereas; the uranium is migrated out in all other units.